Investigation of Correlation between Entrepreneurial Strategies and Resistance Economics Policy in Copper Company - Sharifi, Azizieh (2021)
The purpose of this study was to evaluate the relationship between entrepreneurial strategy and resistance economy policy in Kerman Copper Company. The research is applied and descriptive. The statistical population consisted of 400 experts, supervisors and managers of Shahid Bahonar Copper Company in Kerman. Based on Morgan table, the sample size was 196 people. The standard questionnaire was used for data collection. The validity of the questionnaires was 0.93 and 0.91 respectively and the reliability of the questionnaires was higher than 0.7. Data were analyzed using SPSS software and structural equation modeling test by Amos software. The findings showed that there is a positive and significant relationship between entrepreneurial strategy and resistance economy policy in Kerman Copper Company. On this basis, it can be said that the promotion of entrepreneurial strategies will facilitate the implementation of the Resilience Policy.